Unlocking the Potential of Eugenol-Coformer Co-Amorphous Pairs in Active Packaging Designed for the Controlled Release and Enhanced Antibacterial Activity - Velasquez, E (Elsevier B.V., 2025)
The occurrence of Bacillus cereus in food continues to be a worldwide issue for the food sector and public health due to its prevalence in post-food processing and its role in toxin-induced foodborne illnesses. Antibacterial packaging based on essential oil derivatives and biopolymers arises as an alternative for the elimination or reduction of Bacillus cereus concentration to a harmless level. In this study, the concepts of mechanochemistry to produce eugenol (EU)-phenazine (PHE) pairs and supercritical fluid technology to impregnate this pair in an environmentally friendly way into poly (lactic acid) (PLA) films were used to create a controlled-release antibacterial food packaging material whose biological properties were tested against B. cereus strains. The incorporation of EU-PHE co-amorphous pairs in PLA (10.81 wt%) was verified by XRD, DSC, and SEM. The EU-PHE co-amorphous pairs exhibited an effective diffusion coefficient (6.0 ×10−12 m2 s−1), which is around two orders of magnitude inferior to that of pure EU, thus providing the sustained release of the bioactive agent (EU). The antibacterial PLA films entirely prevented the adhesion of the tested B. cereus strains after 72 h and showed the strongest antibacterial action, with up to a 50 % decrease in the number of bacteria in the broth between 48 and 72 h. © 2025 The Authors